Risks and challenges in Agricultural Marketing in India - Bhatia, Dipti Kiran (2010)
Rural India is the stronghold of the Indian economy which generates more than half of the national income. According to National Council of Applied Economic Research (NCAER), about 74% of Indian population living in the villages that makes India a largest potential rural marketing in the world. Agricultural marketing is a process that starts with a decision to produce a marketable farm product and involves all aspects of market structure or system. The marketing process is full of challenges with some complex problems such as risks and uncertainties which are also the inevitable parameters of modern business. The prevalence of risk in agriculture is imperative to policy makers at national and international levels. Fluctuations in producer incomes, and particularly the threat of loss, may present difficult welfare problems for the producers and the governments. Trading losses at the level of market intermediaries like traders and processors; negatively impact the development of sustainable trading and finance activities in the commodity sectors. This report focuses on the risks that farmers usually come across while selling their produce in agricultural markets especially related to daily price fluctuations. It covers the research done by the various authors about the marketing of agricultural produce and provides some recommendations and suggestions for the improvement in various strategies and methodologies that are being implemented in Indian agricultural marketing system. The particular question posed here is how these agricultural challenges faced by the farmers can be reduced as part of India’s emerging economic development strategies of reforms and liberalisation.